Blood Pressure and Stroke: A Review of Sex- and Ethnic/Racial-Specific Attributes to the Epidemiology, Pathophysiology, and Management of Raised Blood Pressure. Issue 4 (29th March 2022) - Wang, Xia; Carcel, Cheryl; Woodward, Mark; Schutte, Aletta E.
Abstract : Raised blood pressure (BP) is the leading cause of death and disability worldwide, and its particular strong association with stroke is well established. Although systolic BP increases with age in both sexes, raised BP is more prevalent in males in early adulthood, overtaken by females at middle age, consistently across all ethnicities/races. However, there are clear regional differences on when females overtake males. Higher BP among males is observed until the seventh decade of life in high-income countries, compared with almost 3 decades earlier in low- and middle-income countries. Females and males tend to have different cardiovascular disease risk profiles, and many lifestyles also influence BP and cardiovascular disease in a sex-specific manner. Although no hypertension guidelines distinguish between sexes in BP thresholds to define or treat hypertension, observational evidence suggests that in terms of stroke risk, females would benefit from lower BP thresholds to the magnitude of 10 to 20 mm Hg. More randomized evidence is needed to determine if females have greater cardiovascular benefits from lowering BP and whether optimal BP is lower in females. Since 1990, the number of people with hypertension worldwide has doubled, with most of the increase occurring in low- and-middle-income countries where the greatest population growth was also seen. Sub-Saharan Africa, Oceania, and South Asia have the lowest detection, treatment, and control rates. High BP has a more significant effect on the burden of stroke among Black and Asian individuals than Whites, possibly attributable to differences in lifestyle, socioeconomic status, and health system resources. Although pharmacological therapy is recommended differently in local guidelines, recommendations on lifestyle modification are often very similar (salt restriction, increased potassium intake, reducing weight and alcohol, smoking cessation). This overall enhanced understanding of the sex- and ethnic/racial-specific attributes to BP motivates further scientific discovery to develop more effective prevention and treatment strategies to prevent stroke in high-risk populations.